INNOVATIVE-DIDACTIC MODEL OF TEACHING THEORETICAL MECHANICS IN FORMING GENERAL TECHNICAL COMPETENCE - Parmonov Abdultalib Abduvahob (International Scientific and Current Research Conferences, 2026)
This in the thesis future engineers general technician competence to develop aimed at component and develop a meaningful model issued is , then theoretical mechanics science to the profession focused , innovative and interdisciplinary integrated teaching opportunities based on given.